Quality of life among women living in Haor Basin in Bangladesh and its socio-economic predictors - Hiramoni, Fatema Akhter (Intelektual Pustaka Media Utama, 2023)
The Haor region in Bangladesh is a relatively more poverty-driven area than other rural areas of Bangladesh. There is very little information about the quality of life of women living in Haor areas. Therefore, the present study aimed to assess Haor women's quality of life and identify predictors. The data from the project titled ‘Livelihood and Socio-economic well-being of Women Living in Haor Basin: A Cross-sectional Survey’ were utilized in this study. Results showed that household income was lower than that reported in the household income and expenditure survey or HIES Survey 2016 for rural people in Bangladesh. Around half of them actively participated in the household economic decision-making process and one- fifth were satisfied with their household and personal financial condition. Only 30% rated their quality of life as good or very good. Contribution to household income, importance and control over household economic decisions, and household savings and loans, were significantly associated with the overall quality of life and its domains. This study’s findings would help to design and implement policies and development program to improve the living standard of women living in Haor Basin and thus help to achieve the relevant targets under specific sustainable development goals.